PENGARUH KEBIJAKAN BAGASI BERBAYAR PADA MASKAPAI LION AIR TERHADAP KEPUASAN PENUMPANG DI BANDAR UDARA DOMINE EDUARD OSOK SORONG - Rosa Sthefanny Shalsa Maturbongs; Dhiani Dyahjatmayanti (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
This thesis research is motivated by the paid baggage system policy implemented by Lion Air airline in 2019. Lion Air is known as an airline whose services use low cost carrier/LCC with cheap ticket prices and waived baggage fees. For the Papua route, Lion Air is the only airline that operates and reaches the interior of Papua with quite expensive ticket prices. With this policy, it might burden the community, especially the lower middle class. The purpose of this research is to determine the influence and how much influence the Lion Air airline's paid baggage policy has on passenger satisfaction at Domine Eduard Osok Sorong Airport. This research uses a quantitative approach with an analysis technique, namely simple linear regression. The results of this research show that the paid baggage policy at Domine Eduard Osok Sorong Airport has a significant effect on passenger satisfaction due to the significance value obtained where T count (20.695) > T table (1.662). T calculated with a significance level of 0.00 < 0.05 and a value of the coefficient of determination of 0.0831, this means that 83.1% of the variation in changes in passenger satisfaction can be explained by the paid baggage policy. So it can be concluded that Ha is accepted and Ho is rejected.